2015
DOI: 10.1074/jbc.m115.686915
|View full text |Cite
|
Sign up to set email alerts
|

FYCO1 Contains a C-terminally Extended, LC3A/B-preferring LC3-interacting Region (LIR) Motif Required for Efficient Maturation of Autophagosomes during Basal Autophagy

Abstract: Background: FYCO1 binds to LC3 and is involved in transport of autophagosomes. Results: FYCO1 uses a C-terminally extended LIR motif for specific interaction with LC3A/B stimulating autophagosome maturation during basal autophagy. Conclusion:The transport adaptor FYCO1 engages in a specific interaction with LC3A/B to stimulate autophagosome maturation. Significance: This work will lead to an increased understanding of LIR interactions and the role of FYCO1 in autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
135
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(155 citation statements)
references
References 47 publications
16
135
0
Order By: Relevance
“…Yet, induction of transport towards the cell periphery is not the only effect of FYCO1. FYCO1 was recently shown to contribute to the maturation of autophagosomes and phagophores through its LIR domain (Ma et al 2014;Olsvik et al 2015;Dionne et al 2017). Indeed, rare FYCO1 variants some of which contain missense mutations in the LIR domain have recently been associated with inclusion body myositis (G€ uttsches et al 2017) a disease characterized by accumulation of protein aggregates and suspected impaired autophagic degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, induction of transport towards the cell periphery is not the only effect of FYCO1. FYCO1 was recently shown to contribute to the maturation of autophagosomes and phagophores through its LIR domain (Ma et al 2014;Olsvik et al 2015;Dionne et al 2017). Indeed, rare FYCO1 variants some of which contain missense mutations in the LIR domain have recently been associated with inclusion body myositis (G€ uttsches et al 2017) a disease characterized by accumulation of protein aggregates and suspected impaired autophagic degradation.…”
Section: Discussionmentioning
confidence: 99%
“…FYCO1 through its LC3‐interacting region (LIR) motif was shown to be important for the fusion of autophagosomes with lysosomes (Olsvik et al . ) and for the fusion of late endosomes with the plasma membrane (Raiborg et al . ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative hypothesis is that R70 contributes to the binding of LIR domain proteins that then affect autophagosome maturation. For instance, it has recently been observed that FYCO-1, a protein required for autophagosome transport along microtubules [33] binds directly via its LIR domain to a region in LC3A and LC3B that includes R70, thereby affecting autophagosome maturation under basal conditions [34]. The precise mechanisms how a R70H substitution contributes to defective autophagosome maturation will need to be studied in further detail.…”
Section: Discussionmentioning
confidence: 99%
“…LC3-II also contributes to cargo selection by the autophagosome which is achieved via autophagy receptors such as p62/sequestosome-1 [15, 25]. Complete autophagosomes are directed to lysosomes by the cytoskeleton [26, 27] and fusion is directed by the combined actions of Rab7a (Ras-related protein Rab-7a) GTPase, SNARE (soluble NSF [N-ethyl-maleimide-sensitive fusion protein] attachment protein receptor), and HOPS (Homotypic fusion and protein sorting) complexes [2734]. …”
Section: Autophagy a Central Pathway In Biologymentioning
confidence: 99%